Using Activity-Based Costing to Create Transparency and Consistency in Accounting for Division I Intercollegiate Athletics - Heather J. Lawrence; E. Ann Gabriel; Lauren E. Tuttle (University of Kansas Libraries, 2010)
The financial challenges currently faced by NCAA Division I intercollegiate athletics programs have been of interest to academics and practitioners alike. According to the 2004-08 NCAA Revenues and Expenses Report, less than 6% of Division I athletics programs were profitable each year from 2004 to 2008 (Fulks, 2009). For the other 94% of programs, there is a reliance on institutional funding to sustain athletic operations (Fulks). Exacerbating this trend, the economic downturn in the United States is forcing institutions to make difficult spending decisions across all campus programs, including intercollegiate athletics. Currently, there are inconsistencies in the accounting practices of intercollegiate athletic departments; especially as those practices relate to allocation of costs (Sperber, 2000; Thelin, 2000; Zimbalist, 2006). The lack of consistency hinders the ability of institutional leaders to make informed decisions about athletics spending. This cross-disciplinary, conceptual paper examines how Activity-Based Costing (ABC), a prominent management accounting cost allocation method, can be applied to NCAA Division I athletic departments. At a time when expenses are outpacing revenues and reliance on institutional support is great, athletic administrators must be armed with accurate information about the costs associated with the operation of each sport program to help in making difficult financial decisions commonplace in today's economic climate.